2005
DOI: 10.4049/jimmunol.175.1.104
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of Effector T Cells and Fas Ligand on Lupus-Associated B Cells

Abstract: Circulating autoantibodies against dsDNA and chromatin are a characteristic of systemic lupus erythematosus in humans and many mouse models of this disease. B cells expressing these autoantibodies are normally regulated in nonautoimmune-prone mice but are induced to secrete Abs following T cell help. Likewise, anti-chromatin autoantibody production is T cell-dependent in Fas/Fas ligand (FasL)-deficient (lpr/lpr or gld/gld) mice. In this study, we demonstrate that Th2 cells promote anti-chromatin B cell surviva… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
18
1

Year Published

2006
2006
2012
2012

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 20 publications
(20 citation statements)
references
References 87 publications
1
18
1
Order By: Relevance
“…We have shown here and in previous publications that Treg cells can block anti-chromatin Ab production in an in vivo transfer model [4,5,45]. Why, then do older lpr/lpr gld/gld mice develop anti-chromatin Abs even though they have high numbers of Treg cells?…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…We have shown here and in previous publications that Treg cells can block anti-chromatin Ab production in an in vivo transfer model [4,5,45]. Why, then do older lpr/lpr gld/gld mice develop anti-chromatin Abs even though they have high numbers of Treg cells?…”
Section: Discussionmentioning
confidence: 96%
“…Established Th2 cells appear less resistant than Th1 cells to the effects of Treg cells on their cytokine potential. We and others have shown that IFN-γ-producing Th cells are effective at promoting Abs in vivo, including anti-chromatin Abs [44,45]. Furthermore, many studies have shown a preponderance of a Th1-type environment in Fas or FasL-deficient mice [27,46,47].…”
Section: Discussionmentioning
confidence: 99%
“…For L chain usage, plates were coated with either anti-Ig or anti-Ig (Southern Biotechnology Associates) and detected with anti-total Ig-AP (human absorbed; Southern Biotechnology Associates). Plates were developed as described previously (40).…”
Section: Determination Of Hybridoma H and L Chain Isotypesmentioning
confidence: 99%
“…DCs have been shown to both positively and negatively regulate autoantibody production [5][6][7]. Helper T cells, or signals associated with T-cell help, appear to negatively regulate B-cell tolerance [8][9][10][11][12]. It remains unclear as to which helper T-cell populations can support autoantibody production.…”
mentioning
confidence: 99%